The Influence of Age on Changes in Health-Related Quality of Life over Three Years in a Cohort Undergoing Hemodialysis - Unruh, Mark L. (J Am Geriatr Soc, 2008)
OBJECTIVES: To assess the extent to which persons aged 70 and older undergoing hemodialysis (HD) had greater changes in health-related quality of life (HRQOL) over 3 years than younger patients undergoing HD. DESIGN: Longitudinal. SETTING: The Hemodialysis Study (HEMO Study) was a randomized, clinical trial of the effects of HD dose and membrane flux on mortality and morbidity in patients undergoing chronic dialysis. PARTICIPANTS: Secondary analysis of the HEMO Study. MEASUREMENTS: Participants completed the Index of Well-Being (IWB) and the Kidney Disease Quality of Life—Long Form (KDQOL-LF), which also includes the Medical Outcomes Study 36-item Short Form Questionnaire (SF-36) annually. Changes in subjects those aged 70 and older were compared with changes in subjects aged 55 to 69 and 18 to 54. RESULTS: At baseline, 1,813 (98%) of HEMO participants completed HRQOL surveys. Their mean age was 58, 56% were female, 64% were black, and mean duration of dialysis was 3.8 years. In subjects with HRQOL data at the first three annual assessments, there were no substantial mean declines in the SF-36 Physical or Mental Component Summary scales over 3 years. In models incorporating effects of attrition, the differences in average change over 3 years between patients undergoing HD aged 70 and older and the younger cohorts were small in magnitude. There were high rates of adverse HRQOL events in all age groups and significantly higher composite event rates of death or clinically significant decline in HRQOL over 3 years was found in subjects aged 70 and older. CONCLUSION: Although HRQOL was impaired in the population undergoing HD, HRQOL scores at baseline reflect a better-preserved multidimensional quality of life in respondents in the HEMO Study aged 70 and older than in younger patients undergoing HD. There was no substantial relationship between age and average decline in HRQOL score over 3 years in participants in the HEMO Study.